Identification of hub six interferon alpha response genes and immune cell infiltration characteristics in low-grade glioma - Xue Zhang; Shuo Song; Defen Zhou; Hanwei Cui; Jiangan Xie (Scientific Reports)
Abstract Low-grade glioma(LGG) is a prevalent primary brain tumor, and type I interferons(IFN-Is) can exert a multifaceted influence on the regulation of the tumor microenvironment during its initiation and progression. To investigate the role of IFN-Is in the progression of LGG, we screened public databases for features based on IFN-alpha(IFN-α) response genes (IRGs), a risk model was constructe and its relationship to tumor immunity and prognosis was evaluated. In addition, the expression and regulation of IRGs in LGG were further studied in vitro biological function experiments and immunohistochemistry of clinical samples. 20 differential genes associated with LGG-IRGs were found, then 6-IRGs-based signature was found by using of univariate COX, LASSO and SVM-RFE. ROC curves also supported the value of signature. CIBERSORT results demonstrated the crucial role played by these key signature genes in immune response. Additionally, aggregation analysis of relevant immune-related genes revealed that cluster 1 exhibited the lowest expression of RIPK2 and SELL. Moreover, GSVA results suggested that diagnostic immune-related genes may regulate LGG by influencing immune cells. We further validated these findings using external datasets and provided additional evidence supporting the predictive value of signature genes associated with IRGs in LGG through immunohistochemical testing on clinical samples and in vitro experiments. These 6 diagnostic IRGs genes can help differentiate and predict the prognosis and immune status of patients with LGG, thereby providing new strategies for precise and personalized immunotherapy.